Utilization of Corn Oil as a Photocatalyst of Carbon Nanodots for Wastewater Cleaning - Ihwan, Muh Al; Prasetyo, Zuhdan Kun (Jurnal Penelitian Fisika dan Aplikasinya (JPFA), 2021)
Water is a basic need of society. Unfortunately, the availability of clean water is very limited due to the large amount of waste in the waters in various regions in Indonesia. Thus, innovation is needed to purify wastewater. This research utilizes corn oil to reduce the pollution of dye waste, which is a problem for the environment. Corn oil is easy to find so it is suitable to be used to purify water waste. The photocatalyst technique using carbon nanodots of sun-assisted corn oil is an economical and easy-to-obtain method. Carbon nanodots from corn oil are made using the Hydrothermal method at a temperature of 2500oC heated for 3 hours. Carbon nanodots from corn oil are used as a photocatalyst in artificial methylene blue waste solutions. The photocatalyst test process is carried out by varying the amount of carbon dots. The result was observed until the artificial wastewater from methylene blue turned clear by varying a lot of carbon from 2 ml, 4 ml, 6 ml, 8 ml, and 10 ml. When the carbon nanodot content is 8 ml, the fastest time needed to clear methylene blue wastewater is 55 minutes. The fewer or more solutions given, the more time to clear up. These results indicate that carbon nanodots from corn oil can be used for photocatalyst purification of methylene blue wastewater.